Anti-Transgender Ideology, Laws, and Homicide: An Analysis of the Trifecta of Violence - Brightman, Sara (Homicide studies, 2024)
In this study we explore homicides and fatal violence against transgender individuals using the framework of the trifecta of violence—violent ideology, violent policies and laws, and violent actions. In recent years, researchers, activists, and the media, particularly the news media, have been warning that the increase in anti-LGBTQ+ rhetoric, especially but not exclusively online, coupled with a surge in anti-transgender legislation, has resulted in increased instances of violence against the LGBTQ+ community, especially transgender people. In this article we examine patterns of transphobic ideology and rhetoric, anti-trans legislation, and fatal violence against transgender people in the United States from 2015 to 2022. We find that increases in all three occurred over this time period, with all three aspects of the “trifecta” correlated.